DEVELOPING STUDENTS’ DESCRIPTIVE WRITING ABILITY BY USING ANIMATION MOVIE - Bahri, Syamsul; Satriani; Muzkiyah, Nurul (Pusat Riset dan Inovasi Nasional, 2021)
This study's objective is to study how using animated movie might help students improve their writing skills. One class served as the research sample for the pre-experimental methodology used in this study. In the first year of the MA Muhajirin, As'adiyah Kampiri, served as the research sample. Twenty students made up the study's sample. In order to select the sample for the study, the researcher employed the cluster random sampling technique and chose X A. Their understanding of the subject matter for text writing was made simple and enjoyable by the audio and visual mix. It was also acceptable for junior high school kids to get excited and interested in writing in order to hone their descriptive text-writing abilities. Writing tests were used to gather data on the students' descriptive writing abilities, which were then evaluated using SPSS 20. There were noticeable improvements, as seen by the pre-test and post-test results. The pupils' experimental post-test score of (82.11) was greater than their pre-test score, which served as evidence (52.63). The results also revealed that the probability value (0.00) was less than the level of significance (0.05). Based on the findings, the researcher concluded that using animation movies could help students in their first year of MA strengthen their descriptive writing skills. As'adiyah Kampiri Muhajirin.